Paper Mills for research writing and publication: A threat to the integrity of science - Shah, Jay; Shah, Jenifei (Journal of Kathmandu Medical College, 2021)
The reliability of publication affects evidence-based science. In recent years, science has come under increasing scrutiny for its trustworthiness because of the misconduct of a few researchers, authors, and publishers involved in the unethical behaviour of research writing and publication. There has been an exponential increase in research output worldwide, and many publications are of questionable credibility due to “Paper Mills.” These are profit-oriented, illegal, and unethical organisations working in the shadow to produce papers on demand, or sell readymade papers for a price. All stakeholders: researchers, authors, readers, journal publishers, and all of the academia need to be aware of “Paper Mills” to minimise scientific misconduct.